Determining concrete structure condition rating based on concrete compressive strength - Wiyanto, Henny; Makarim, Chaidir Anwar; Gondokusumo, Onnyxiforus; Siregar, Januar Parlaungan; Irawan, Agustinus Purna; Cionita, Tezara; Najid, Najid (MDPI, 2022)
The need for concrete condition assessment for existing buildings increases because of high disaster vulnerability levels, as well as a large number of buildings that have reached their age of use. Currently, there is not any standard reference for assessing concrete condition rating yet, so a concrete condition assessment method that can be measured quantitatively needs to be developed. The developed concrete condition assessment method combines concrete condition assessment based on visual inspection and testing. Assessment measures start with an assessment of visual inspection results, which is continued with concrete compressive strength testing. This article contains a concrete condition assessment based on concrete compressive strength testing. This method determines the concrete condition rating scale using five condition ratings as a reference for building condition assessment. The limit value of each condition rating is taken from concrete compressive strength values that are structurally sufficient, according to the structural concrete requirement code for buildings. Concrete compressive strength values have resulted from non‐destructive tests and destructive or loading tests. Building condition rating (BCR) value determination factors in the effect of structure element damage towards building structure and concrete testing result accuracy rating, and also can decrease inaccuracy towards concrete quality condition rating determination on scale limit values, and minimize error risks in determining damage condition rating. The result-ing method has the advantage of assessing structure element condition rating and building condition rating (BCR) that can be measured quantitatively, has five assessment scale ratings that can portray building conditions having to be demolished, and calculates structure element critical weight.